The impact of body mass index on treatment outcomes for patients with low-intermediate risk prostate cancer. Issue 1 (December 2016) - Yamoah, Kosj; Zeigler-Johnson, Charnita; Jeffers, Abra; Malkowicz, Bruce; Spangler, Elaine; Park, Jong; Whittemore, Alice; Rebbeck, Timothy
Abstract Background Little is known about the relationship between preoperative body mass index and need for adjuvant radiation therapy (RT) following radical prostatectomy. The goal of this study was to evaluate the utility of body mass index in predicting adverse clinical outcomes which require adjuvant RT among men with organ-confined prostate cancer (PCa). Methods We used a prospective cohort of 1, 170 low-intermediate PCa risk men who underwent radical prostatectomy and evaluated the effect of body mass index on adverse pathologic features and freedom from biochemical failure (FFbF). Clinical and pathologic variables were compared across the body mass index groups using an analysis of variance model for continuous variables or χ2 for categorical variables. Factors related to adverse pathologic features were examined using logistic regression models. Time to biochemical recurrence was compared across the groups using a log-rank survivorship analysis. Multivariable analysis predicting biochemical recurrence was conducted with a Cox proportional hazards model. Results Patients with elevated body mass index (defined as body mass index ≥25 kg/m2 ) had greater extraprostatic extension (p  = 0.004), and positive surgical margins (p  = 0.01). Elevated body mass index did not correlate with preoperative risk groupings (p  = 0.94). However, when compared with non-obese patients (body mass index <30 kg/m2 ), obese patients (body mass index ≥30 kg/m2 ) were much more likely to have higher rate of adverse pathologic features (p  = 0.006). In patients with low- and intermediate- risk disease, obesity was strongly associated with rate of pathologic upgrading of tumors (p  = 0.01 andp  = 0.02), respectively. After controlling for known preoperative risk factors, body mass index was independently associated with ≥2 adverse pathologic features (p  = 0.002), an indicator for adjuvant RT as well as FFbF (p  = 0.001). Conclusions Body mass index of ≥30 kg/m2 is independently associated with adverse pathologic features, which is an indicator for additional RT, particularly in patients with low-intermediate risk disease. Future studies may determine if this select group of patients may be best treated with definitive RT to reduce toxicity from additional RT following radical prostatectomy. We propose including body mass index in clinical decision-making for appropriate treatment recommendation for patients with low-intermediate risk PCa.